Penerapan Kegiatan Maulid Dibā’ Dalam Meningkatkan Karakter Religius Santri - Khoirunnisya, Rika; Al Ghifary S, Muh Ubaidillah (Prodi Pendidikan Keagamaan Islam, 2024)
Our country is faced with a moral crisis and character decline such as violence, sexual harassment, teenage promiscuity, therefore religious value activities are very important to implement, not only through formal institutions but can be through non-formal institutions such as learning the Koran, learning groups or activities that are da'wah. Data collection techniques used are through observation, interviews, and documentation. The data analysis techniques used is data reduction, data presentation and conclusion. The results of this study indicate that: the implementation of maulid Dibā' activities in Hasbiyallah Islamic boarding school is threefold, namely a. planning b. implementation and c. evaluation of Diba' maulid activities within a period of once every two weeks or once a month, the improvement of religious character through Dibā' maulid is divided into two types, namely: divine value, namely increasing love for Allah and the Messenger, praying on time with their own awareness, diligently reading the Qur'an, and human value, namely discipline, honesty, kindness, responsibility, courtesy, respect, and good manners. Supporting factors in the process of improving the religious character of santri are self-motivation, the encouragement to obey worship to Allah SWT, religious-based activities, supporting infrastructure and a bad environment, and inhibiting factors are lack of awareness of religiosity, lack of religious knowledge and a bad environment.